2018
DOI: 10.4081/ijfs.2017.6921
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of protein spoilage in fresh and defrosted crustaceans and cephalopods stored in domestic condition

Abstract: In relation to consumer demand, crustaceans and cephalopods are sold as both fresh and defrosted. It is well known that total volatile basic nitrogen (TVB-N) and volatile amine values, especially, biogenic amines and biogenic amine index, are expression of freshness of fish products, but there is a lack of knowledge of their acceptability limits, for crustaceans and cephalopods. In order to assess these limits, real-time shelf life tests were carried out, relating the results of TVB-N, biogenic amines and BAI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…In the first phase, the NH 3 concentration increases slowly although in the refrigerator, since the enzymatic and bacteria growth decomposes the fish proteins even at a temperature of a few degrees [ 72 ], so producing nitrogen volatile compounds that indicate the spoiling of the fish. This trend has accelerated after the defrosting (from the 20th day) reaching a peak value of 274 ppm (i.e., 190.5 mg/m 3 ) after about 4 days, then the NH 3 concentration reduced indicating an advanced decomposition of fish proteins, as already reported in [ 73 ] ( Figure 23 b). A CO 2 concentration near to the lower limit of the MiCS-5914 sensor (i.e., 400 ppm) was detected before the box left the freezer, values ascribable to the environmental concentration inside the box; in fact, once the box was extracted from the freezer and removed the plastic wrap, the CO 2 concentration is increased slightly around the value of 500 ppm, due to the indoor environment.…”
Section: Discussionsupporting
confidence: 77%
“…In the first phase, the NH 3 concentration increases slowly although in the refrigerator, since the enzymatic and bacteria growth decomposes the fish proteins even at a temperature of a few degrees [ 72 ], so producing nitrogen volatile compounds that indicate the spoiling of the fish. This trend has accelerated after the defrosting (from the 20th day) reaching a peak value of 274 ppm (i.e., 190.5 mg/m 3 ) after about 4 days, then the NH 3 concentration reduced indicating an advanced decomposition of fish proteins, as already reported in [ 73 ] ( Figure 23 b). A CO 2 concentration near to the lower limit of the MiCS-5914 sensor (i.e., 400 ppm) was detected before the box left the freezer, values ascribable to the environmental concentration inside the box; in fact, once the box was extracted from the freezer and removed the plastic wrap, the CO 2 concentration is increased slightly around the value of 500 ppm, due to the indoor environment.…”
Section: Discussionsupporting
confidence: 77%
“…First, the higher TVBN contributes to the off-flavor of meat owing to the rise in byproducts such as acid compounds and mineral nitrogen [49]. Second, higher TVBN values provokes a rotten and ammonium odor from foods [50]. These sensory responses were similarly observed in the actual sensory test.…”
Section: Physicochemical Qualitiesmentioning
confidence: 83%
“…53 Protein content of meat is destroyed by bacterial growth and changed to some volatile basic nitrogen compounds such as ammonia, trimethylamine, and dimethylamine. 54 Dong et al reported that TVB-N content in shrimps packaged with polyethylene films containing rosemary and cinnamon EOs was significantly lower compared to those packaged in film without the EOs (P < 0.05). 47 Similarly, the lowest TVB-N value belonged to the shrimps packed in films incorporated with 1% (w/w) rosemary/1% (w/w) cinnamon EOs.…”
Section: Discussionmentioning
confidence: 99%